Recent genome resequencing paraded COBRA-Like gene family roles in abiotic stress and wood formation in Poplar - Sajjad, Muhammad; Ahmad, Adeel; Riaz, Muhammad Waheed; Hussain, Quaid; Yasir, Muhammad; Lu, Meng‐Zhu (Frontiers in Plant Science, 2023)
Cell wall determines the mechanical properties, serves as a barrier against plant stresses and allows the cell division and growth processes. The COBRA-Like (COBL) gene family encodes a putative glycosylphosphatidylinositol (GPI)-anchored protein that controls cellulose deposition and cell progression in plants by contributing in microfibril orientation of cell wall. Despite being studied in different plant species, there is a dearth of a comprehensive global analysis of COBL genes in pPoplar. Poplar is employed as a model woody plant to study abiotic stress and biomass production in tree research. Improved genome resequencing enabled a comprehensive exploration of the evolution and functional capacities of PtrCOBLs in Poplar. Phylogeny analysis discerned and classified PtrCOBLs into 2 groups resembling the Arabidopsis COBL family, Ggroup I genes possess longer proteins but have fewer exons than gGroup II. Analysis of gene structure and motifs revealed, PtrCOBLs maintained a rather stable motif and exon-intron pattern across members of the same group. Synteny and collinearity analyses exhibited that evolution of the COBL gene family was heavily influenced by gene duplication events. PtrCOBL genes had undergone both segmental duplication and tandem duplication, followed by purifying selection. Promotor analysis flaunted various phytohormone, growth and stress related (MYB, ABA, MeJA, SA, AuxR, ATBP1 etc.) cis-elements. Likewise, 29 Ptr-miRNAs of 20 families were found targeting 11 PtrCOBL genes. PtrCOBLs were found localized at the plasma membrane and extracellular